2020
DOI: 10.1007/s10695-020-00837-1
|View full text |Cite
|
Sign up to set email alerts
|

Spotted wolffish (Anarhichas minor) sperm cryopreservation in 5-mL cryovials

Abstract: In spotted wolffish Anarhichas minor aquaculture, cryopreservation is used to secure sperm availability throughout the entire spawning season. Under current protocols, sperm is cryopreserved in 0.5-mL straws. This implies thawing a considerable number of straws for insemination with cryopreserved sperm. In this work, we scale up the spotted wolffish sperm cryopreservation procedure through the development of a protocol for sperm cryopreservation in 5-mL cryovials. Different freezing (distances from the liquid … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 18 publications
0
7
0
Order By: Relevance
“…Unpredictable sperm quality and quantity require maintenance of large numbers of males, which results in poor utilization of hatchery facilities. Beirao et al (2020) observed a desynchronization between male and female maturation, with males maturing earlier than females. The level of plasma androgens (11-ketotestosterone; 11-Kt) that direct testicular development is considered low in spotted wolffish, compared to other fish species, possibly as a result of physiological stress associated with a suboptimal rearing environment usually mediated by the hormone cortisol.…”
Section: Broodstock and Egg Incubationmentioning
confidence: 95%
“…Unpredictable sperm quality and quantity require maintenance of large numbers of males, which results in poor utilization of hatchery facilities. Beirao et al (2020) observed a desynchronization between male and female maturation, with males maturing earlier than females. The level of plasma androgens (11-ketotestosterone; 11-Kt) that direct testicular development is considered low in spotted wolffish, compared to other fish species, possibly as a result of physiological stress associated with a suboptimal rearing environment usually mediated by the hormone cortisol.…”
Section: Broodstock and Egg Incubationmentioning
confidence: 95%
“…This method provides an initial assessment of the motility and is often used in fertilization trials [110]. Nonetheless, the use of computer-assisted sperm analysis systems (CASA) provides a more objective evaluation and has also been employed in spotted wolffish sperm quality studies [25,102,106,111]. The CASA systems, besides the percentage motility, measure different sperm swimming velocity parameters, such as curvilinear velocity (VCL) or straight-line velocity (VSL), parameters associated with the trajectory such as linearity (LIN), and other parameters such as wobble of the sperm head; for a detailed description, see [112].…”
Section: Quality Evaluationmentioning
confidence: 99%
“…It is often difficult to find spermiating males and with enough sperm volume at the end of the spawning season [1], and this represents a challenge to fertilize the last egg batches. Consequently, the development of sperm storage techniques has been extensively researched [25,102,105,106,109,111]. Cryobanking of the sperm of genotyped broodstock populations is justified in order to control undesirable inbreeding levels.…”
Section: Storagementioning
confidence: 99%
See 2 more Smart Citations